Inside the castle : law and the family in 20th century America - Grossman, Joanna L. (Princeton University Press, 2011)
Inside the Castle is a comprehensive social history of twentieth-century family law in the United States. Joanna Grossman and Lawrence Friedman show how vast, oceanic changes in society have reshaped and reconstituted the American family. Women and children have gained rights and powers, and novel forms of family life have emerged. The family has more or less dissolved into a collection of independent individuals with their own wants, desires, and goals. Modern family law, as always, reflects the brute social and cultural facts of family life.